UJI AKTIVITAS ANTIOKSIDAN DARI EKSTRAK ETANOL DAUN SIDAGURI (Sida rhombifoliaL.) DENGAN METODE DPPH(1,1-Difenil-2-Pikrilhidrazil) - Khairunnisa Khairunnisa; Ridwanto Ridwanto (CV. Adiba Aisha Amira, 2024)
Sidaguri (Sida rhombifolia L.) is a plant that contains alkaloids, flavonoids, saponins, tannins, and triterpenoids. Sidaguri plants contain antioxidants. Antioxidants are chemical compounds that can donate electrons to reactive free radicals so that they are not reactive and stable so that they can prevent the oxidation process in the body. This study aims to determine the class of chemical compounds contained in simplicia and sidaguri leaf extract and the antioxidant activity of sidaguri leaf extract. The research stages include the collection and processing of simplicia. Sidaguri leaf extract (Sida rhombifolia L.) was obtained by maceration method using 70% ethanol as solvent. Examination of the characteristics of simplicia powder. The extract whose solvent has been evaporated to become a thick extract is then carried out for phytochemical screening. The ability of the extract as an antioxidant was determined by reducing the DPPH radical (1,1-Diphenyl-2-picrylhydrazyl) with various extract concentrations 1500 μg/ml, 2000 μg/ml, 2500 μg/ml, 3000 μg/ml, 3500 μg/ml, 4000 μg/ml. The results of the extraction of sidaguri leaves obtained were 34.82 g of thick extract. The results of the phytochemical test of sidaguri leaves contain secondary metabolites, namely alkaloids, steroids, flavonoids, tannins, and saponins. The final result of the DPPH test is that the radicals change color from purple to yellow and their absorption is measured by UV-Vis spectrophotometry at a wavelength of 517 nm. The results of the antioxidant activity test carried out resulted in an IC₅₀ value of 2351.53 μg/ml which indicated that the antioxidant activity was very weak.